5y-y+1/3=6y+1/5

5y - y + 1/3 = 6y + 1/5
=>  4y + 1/3 = 6y + 1/5
=>  1/3 - 1/5 = 6y -4y 
=> (5 - 3)/15 = 2y  ( taking lcm)
=> 2/15 = 2y
=>  y = 1/15

 If the question is 5y - (y+1)/3 = 6y + 1/5
=>{ 15y - ( y + 1)}/3 = (30y  + 1)/5   ( taking L.C.M)
=> (15y - y - 1)/3 = (30y + 1) /5
=> ( 14y - 1) * 5 = (30y + 1) * 3
=> 70y - 5 = 90y + 3
=> 20y = -8
=> y = -8/20
=> y = -2/5
Hope this helped you!

  • 14
5y-y+1/3=6y+1/5
5y/3-y/3+1/3=6y/5+1/5
4y/3+1/3=6y/5+1/5
4y/3-6y/5=1/5-1/3
20y-18y/15=3/15-5/15
2y=-2
y=-2/2
y=-1
  • -2
What are you looking for?